Tinjauan literatur: Evaluasi Kepatuhan Terapi Obat Pada Pasien Diabetes Melitus 2 Menggunakan Media edukasi Booklet - Tamimah, Diyanah Fauziyah; Putri , Mukarromah Dita; Salsabila, Elsyifa (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Type 2 diabetes mellitus is a chronic disease that requires long-term treatment and continuous management, with its prevalence increasing in Indonesia. Patient adherence to treatment is crucial for effective disease control. This article explains that the use of booklets as educational media can play an important role in improving treatment adherence among patients with type 2 diabetes. A Systematic Literature Review was conducted following the PRISMA guidelines by searching PubMed and Google Scholar for articles published between 2015 and 2025. The findings show that booklets are effective when used independently or in combination with other educational methods; however, combining them with direct education from healthcare professionals yields more optimal results in improving adherence. Factors such as age, educational level, family support, and ease of access to information influence the success of this intervention. Booklets are superior to other educational media because they can be reread, provide comprehensive information, and are affordable without requiring advanced technology. The results indicate that booklets are an effective and valuable educational tool to enhance treatment adherence among patients with type 2 diabetes mellitus. Therefore, it is recommended that they be incorporated into chronic disease management strategies in primary healthcare facilities.